1990
DOI: 10.1007/bf00006011
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content of sediments in the Calcasieu River/Lake Complex, Louisiana

Abstract: The heavy metals Cd, Cr, Cu, Pb, Hg, Ag, and Zn, and the metalloid As were measured in surface sediments at permanent stations located in the Calcasieu River/Lake Complex . The relationships among metal concentrations in different areas of the system were investigated to determine sources, source strength, and transport . The point-source inputs of heavy metals were assumed to be industrial outfalls (Bayou d'Inde) and sewage outfalls (Bayou d'Inde and Contraband Bayou) . Although these inputs have not seriousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…The data obtained shows that the trend of occurrence of the trace metals in the river sediments was: Zn > Cu > Cr > Ni > Pb > Cd. The values got in this study for these metals were higher than the corresponding values for Tyume River [17] and Calcasieu River/Lake [18]. However, the levels of Pb and Zn reported by Ellaway et al [19] for sediments of Yarra River/Estuary (Australia) were higher than the corresponding Kubanni River values.…”
Section: Chemical Fractionation Of Trace Metals In Kubanni River Sedicontrasting
confidence: 76%
“…The data obtained shows that the trend of occurrence of the trace metals in the river sediments was: Zn > Cu > Cr > Ni > Pb > Cd. The values got in this study for these metals were higher than the corresponding values for Tyume River [17] and Calcasieu River/Lake [18]. However, the levels of Pb and Zn reported by Ellaway et al [19] for sediments of Yarra River/Estuary (Australia) were higher than the corresponding Kubanni River values.…”
Section: Chemical Fractionation Of Trace Metals In Kubanni River Sedicontrasting
confidence: 76%
“…This result is in agreement with the previously reported localized nature of the contamination within the bayou (1). A study of the chemical speciation of metals bound to sediments collected in southwest Louisiana has shown that Ͼ90% of Cu, 80% of Cr, 60% of Pb, and 60% of Zn are bound to organic and residual binding sites (13,14).…”
Section: Resultssupporting
confidence: 92%
“…Since the early 1940s, this bayou has been used to receive industrial and municipal outfalls and is locally infamous for its level of contamination (1)(2)(3)(4)(5)(6). Since this study was attempting to determine if metals bound to sediments could be extracted by weak natural inorganic and organic acids, the U.S. EPA TCLP method (7) was designed to provide an extraction procedure that would prove whether extracted metals (or organics) would exceed the primary drinking water standards for Maximum Contaminant Levels (MCLs) (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenhouse activity is important in agricultural production. Global environmental issues, is deeply thoughtful and reflective as to how environmental science might be deployed in environmental management [12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%